98.0k views
4 votes
Can someone teach me how to solve rational equations step-by-step. This is not a graded assignment.

Can someone teach me how to solve rational equations step-by-step. This is not a graded-example-1
User ShinNoNoir
by
4.6k points

1 Answer

5 votes

To solve this question, follow the steps below.

Step 01: Factor the denominator of each fraction using (b - 3).

First,


\begin{gathered} b^2-3b \\ b(b-3) \end{gathered}

Second,


\begin{gathered} b^3-3b^2 \\ b^2(b-3) \end{gathered}

Third,


(b-3)

So, the expression is:


(1)/(b(b-3))+(b^2-3b-4)/(b^2(b-3))=(1)/((b-3))

Step 02: Write all fractions together using b²(b-3) as a denominator.


(b*1+b^2-3b-4=b^2*1)/(b^2(b-3))

Solve the multiplications and then the additions/subtractions in the numerator.


\begin{gathered} (b+b^2-3b-4=b^2)/(b^2(b-3)) \\ (b^2-2b-4=b^2)/(b^2(b-3)) \end{gathered}

Step 03: Remove the denominator.

Since both sides are divided by the same number, you can remove it.


b^2-2b-4=b^2

Step 04: Write all numbers on the same side of the equation.

To do it, subtract b² from both sides.


\begin{gathered} b^2-2b-4=b^2 \\ b^2-2b-4-b^2=b^2-b^2 \\ -2b-4=0 \end{gathered}

Step 05: Solve for b.

To do it, add 4 to both sides and then divide the sides by -2.


\begin{gathered} -2b-4+4=0+4 \\ -2b=4 \\ (-2b)/(-2)=(4)/(-2) \\ b=-2 \end{gathered}

Answer: b = -2.

User Ewbi
by
5.5k points